1986
DOI: 10.1254/jjp.42.297
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Action of Mast Cell Stabilizers against Ethanol-Induced Gastric Les ons in Rats

Abstract: Abstract-We examined the effects of FPL-52694 and disodium cromoglycate (DSCG), mast cell stabilizers, on HCI ethanol-induced gastric lesions in rats and investigated the factors involved in their protection.Oral (p.o.) administration of 1 ml of HCI ethanol (60% in 150 mM HCI) induced linear hemor hagic lesions in the gastric mucosa within 1 hr. FPL-52694 (1-30 mg/kg), given both p.o. and intraperitoneally (i.p.), prevented these lesions in a dose-related manner. DSCG (3-30 mg/kg) also dose-dependently reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…In addition, this effect was also impaired by either indomethacin pretreatment or desensitization of the capsaicin-sensitive afferent neurons, indicating that the motility effect of intragastric capsaicin is paralleled by a reduction in gross mucosal injury. These results support our previous observation that a variety of compounds showed cytoprotection at the doses that inhibit gastric motility (6)(7)(8). Inhibition of gastric motility may lead to flattening of the mucosal foldings and decreases the mucosal vulnerability to irritants, resulting in prevention of the fold-related band-like lesions (8,19).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, this effect was also impaired by either indomethacin pretreatment or desensitization of the capsaicin-sensitive afferent neurons, indicating that the motility effect of intragastric capsaicin is paralleled by a reduction in gross mucosal injury. These results support our previous observation that a variety of compounds showed cytoprotection at the doses that inhibit gastric motility (6)(7)(8). Inhibition of gastric motility may lead to flattening of the mucosal foldings and decreases the mucosal vulnerability to irritants, resulting in prevention of the fold-related band-like lesions (8,19).…”
Section: Discussionsupporting
confidence: 92%
“…Gastric motility was measured using a miniature balloon according to the previously published method (6). Briefly, under ether anesthesia, a balloon, the support catheter and another catheter for intragastric administration of drug were placed in the glandular stomach through an incision of the forestomach.…”
Section: Determination Of Gastric Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although a variety of hypotheses have been postulated concerning the mechanism of gastric cytoprotection -an increase of mucus/HCOj secretion and mucosal blood flow, inhibition of gastric motility, and dis solution of mucosal folds [15][16][17][18], none of them was without argument. The present study afforded a useful information about a relationship between the phenomena of cy toprotection and alkaline secretion.…”
Section: Discussionmentioning
confidence: 99%
“…26) It has been reported that an increase in gastric mucosal blood flow is observed after treatment with mild irritants 32) and that inhibition of the increase in mucosal blood flow by indomethacin, N G -nitro-L-arginine methyl ester (L-NAME), or sensory ablation, aggravates mucosal lesions resulting from strong irritants. [32][33][34] Based on such evidence, the mucosal microcirculation is believed to play an important role in mucosal protection by removing back-diffused acid in the mucosa and transporting humoral factors involved in cytoprotection into the epithelial cells. It has been suggested that gastric motility changes play a role in the development and prevention of gastric lesions following both stress and administration of nonsteroidal anti-inflammatory drugs.…”
Section: -4 the Mechanism Of Cytoprotectionmentioning
confidence: 99%